Comparison of Surgical Outcomes Following Percutaneous Pedicle Screw Fixation and Traditional Open Pedicle Screw Fixation for Thoracolumbar Fractures Without Neurological Deficit - Paudel, Kumar; Lamichhane, Somraj; Jha, Rajiv (Journal of Nepal Health Research Council, 2024)
Background: Traumatic thoracolumbar fractures are frequently encountered in blunt trauma patients. The Open pedicle screw fixation has been proven to be effective in stabilizing fractures, deformity correction, early mobilization and improving long term quality of life of patients with thoracolumbar fracture. Percutaneous pedicle screw fixation is a minimally invasive approach that minimizes the tissue injury, enhances early recovery and facilitates rehabilitation program. Objectives: To compare the surgical outcomes of percutaneous versus open pedicle screw fixation for thoracolumbar fractures without neurological deficit. Single center, Prospective, Comparative studyMethods: A total of 34 patients with thoracolumbar fractures with intact neurology were treated with either percutaneous or open pedicle screw fixation between February 1st 2023 to March 1st 2024 at the National trauma center , Kathmandu. There were 17 patients in each group. The perioperative clinical and radiological parameters were collected using a preformed pro forma. Postoperatively follow-up was conducted at post op day 1, during discharge and 3 months. The clinical and radiological outcomes of percutaneous and open pedicle screw fixation were analyzed and compared.Results: This study included 24(70.6%) males and 10(29.4%) females. The mean age was 40.73 Â±15.44 years. There was a statistically significant difference between percutaneous and open pedicle screw with regard to intraoperative blood loss, fluoroscopy time, operative duration, deambulation day and overall hospital stay (p<0.05). Overall, there was a statistically significant improvement in overall pain perception at discharge and three month follow up in both groups. The kyphosis correction in percutaneous group was similar to open pedicle screw fixation technique (mean cobbs angle correction of 4.7 degree).Conclusions: The percutaneous approach has several advantages over the open pedicle screw fixation with regard to less intraoperative blood loss, less postoperative pain, early deambulation, no was a statistically complications and shorter hospital stayKeywords: Open pedicle screw; percutaneous pedicle screw fixation; thoracolumbar fracture.